ARISTOTLE’S POETICS: A CRITIQUE - F.O, Ekevere,; EA, Ikoro,; CC, Omessah (IJRDO - Journal of Social Science and Humanities Research, 2016)
This paper critically examines Aristotle’s Poetics. We begin this discourse by beginning our analysis of Aristotle’s Poetics with an exposition on the man Aristotle, vis-à-vis the socio-cultural milieu that influenced his thoughts and inspired his creative genius. The basic concepts in the poetics were also explained to enhance a clearer understanding of the study. We further did an analytical overview of the Aristotle Poetics. Finally, we gave an overview of the thought of Augusto Boal towards the Aristotle poetics.